Sleep Surface Engineering: A Study on the Pressure Distribution of Air and Sponge Mattresses (International Journal of Scientific Research in Science and Technology, 2025)
This study compared air and sponge mattress pressure distribution and efficiency for different sleeping postures. Statistical tests, PCA, and clustering assessed pressure relief effectiveness. Air mattresses showed superior pressure redistribution and comfort. T-tests and ANOVA showed significantly lower peak pressures with air mattresses, regardless of posture. PCA identified key pressure patterns, clearly separating mattress types and highlighting air mattress conformity. Clustering grouped subjects by pressure patterns, showing more homogenous, lower-pressure groups on air mattresses, suggesting greater comfort. Sponge mattresses exhibited more variable pressure. Results indicate air mattresses offer superior pressure redistribution, potentially improving sleep and reducing pressure ulcers. Future research should examine long-term effects, optimal pressure settings, and therapeutic benefits.
Keywords: pressure distribution; pressure efficiency; ANOVA; PCA; Statical analysis